42CrMo-based self-lubricating material with surface texture soft coating composite interface structure and preparation method of 42CrMo-based self-lubricating material
By depositing WS2 soft coating on the 42CrMo steel substrate material and preparing composite texture fill lubricant, the problem of coordination between lubricating performance and bearing capacity of the friction interface under complex working conditions is solved, and the tribological properties of high stability and low friction coefficient are achieved.
Patent Information
- Application Number
- CN202411738677.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The prior art is difficult to coordinate the friction interface lubrication performance and bearing capacity under complex working conditions such as wide temperature range and high load, and the lubricating layer coverage is insufficient, resulting in unstable friction interface lubrication performance.
Using 42CrMo steel as the base material, a WS2 soft coating was deposited and a composite texture was prepared on its surface, including a honeycomb-arranged hexagonal unit and regular polygonal groove, filled with lubricant Sn-Cu-Zn and reinforced phase TiB2.
During the friction and wear process, a composite lubricating layer with sufficient coverage is formed, which improves the lubricating performance stability of the friction interface, and significantly reduces the friction coefficient and wear rate while ensuring the load-bearing capacity.
Smart Images

Figure HDA0005162105810000011 
Figure HDA0005162105810000021 
Figure HDA0005162105810000022
Abstract
Description
Technical Field
[0001] The invention relates to a 42CrMo-based self-lubricating material with a composite interface structure and a preparation method thereof, wherein the composite interface structure is composed of a WS2 soft coating and a surface texture of a filling lubricant Sn-Cu-Zn and a reinforcement phase TiB2. Background Art
[0002] Friction consumes 1 / 3-1 / 2 of the world's primary energy, and wear causes about 80% of mechanical equipment parts to fail. About 50% of serious equipment accidents are caused by lubrication failure and excessive wear. Due to the rapid development of high-end equipment in the fields of metallurgy, energy, and aviation, their bearings, sliders and other friction parts are often in complex working conditions such as wide temperature range and high load. In recent years, surface texturing technology has effectively promoted the vigorous development of texture tribology. By combining the texturing of the friction surface with the solid self-lubricating technology, the texture acts as a storage device for solid lubricants, providing a "secondary lubrication supply" for the friction pair; at the same time, the texture itself has a friction reduction effect, which can play a synergistic friction reduction effect of "1+1>2", thereby improving the tribological properties of the base material. This method has been widely recognized by scholars at home and abroad.
[0003] However, due to the complex and changeable working conditions of different high-end equipment and the random film-forming behavior of the solid lubricating phase on the friction surface, the traditional friction interface still has the following problems under complex working conditions such as wide temperature range and high load: (1) The surface texture of the filled lubricating phase lacks the optimization design method of the structural size and position distribution, which makes it difficult to coordinate the lubrication performance and bearing capacity of the friction interface; (2) The lubricating layer coverage of the friction interface is insufficient under complex working conditions, which makes the lubrication performance of the friction interface unstable. Therefore, in order to meet the application requirements of mechanical equipment friction parts with excellent anti-friction and wear resistance under complex working conditions such as wide temperature range and high load, it is a technical problem to be solved in the field of solid self-lubricating materials to develop a new friction interface structure that takes into account both lubrication performance and bearing capacity of the friction interface, and has sufficient lubrication layer coverage and stable lubrication performance. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure and a preparation method thereof in view of the deficiencies in the above-mentioned prior art. The structural optimization of the surface texture and the composite of a soft metal lubricant and a lubricating coating are introduced into the interface construction of the self-lubricating material, thereby improving the lubrication performance while ensuring the bearing capacity of the interface. The prepared 42CrMo-based self-lubricating material has stable and excellent friction reduction and wear resistance, and effectively improves the tribological properties of the 42CrMo steel material.
[0005] The technical solution adopted by the present invention to solve the above-mentioned problems is:
[0006] A 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure, which uses 42CrMo steel as a base material, deposits a WS2 soft coating on the surface of the base material, and the surface of the WS2 soft coating is processed with a composite texture; the composite texture is composed of a plurality of hexagonal units arranged in a honeycomb shape, grooves are provided between any adjacent hexagonal units, and a regular polygonal groove is provided in the middle of each hexagonal unit; the grooves and regular polygonal grooves of the composite texture are filled with lubricant Sn-Cu-Zn and a reinforcing phase TiB2.
[0007] Furthermore, the groove depth and the groove depth of the composite texture are both greater than the thickness of the WS2 soft coating.
[0008] Furthermore, each hexagonal unit is a regular hexagon with a side length of 1.5 to 2 mm; the width of the groove is 300 to 400 μm, and the depth of the groove is 100 to 200 μm; a regular polygonal groove is provided in the middle of each regular hexagonal unit, and the regular polygonal groove coincides with the geometric center of the regular hexagonal unit; the side length of the regular polygonal groove is 0.6 to 0.8 mm, and the depth is 100 to 200 μm.
[0009] Furthermore, the regular polygonal groove is preferably a regular hexagonal groove.
[0010] Furthermore, the thickness of the WS2 soft coating is 50 to 80 μm.
[0011] The present invention also provides a method for preparing the above-mentioned 42CrMo-based self-lubricating material having a surface textured soft coating composite interface structure, the main steps of which are as follows:
[0012] 1) A WS2 soft coating with a thickness of 50 to 80 μm was prepared on the surface of a substrate 42CrMo steel by a magnetron sputtering deposition process;
[0013] 2) A composite texture is prepared on the surface of the WS2 soft coating by a laser marking process; the composite texture is composed of a plurality of hexagonal units arranged in a honeycomb shape, grooves are provided between any adjacent hexagonal units, and a regular polygonal groove is provided in the middle of each hexagonal unit;
[0014] 3) Spherical powder containing lubricant Sn-Cu-Zn and reinforcing phase TiB2 is infiltrated and filled into the grooves and regular hexagonal grooves of the composite texture through a high-temperature infiltration process, thereby forming the 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure.
[0015] Preferably, in step 1), the 42CrMo steel substrate is first sandblasted, and then fully cleaned and dried, and then the WS2 soft coating is deposited by magnetron sputtering under vacuum conditions. The grain size of the corundum used for sandblasting is 120-140 mesh, and cleaning is generally performed by alcohol ultrasonic cleaning.
[0016] According to the above scheme, in step 1), the main process parameters of magnetron sputtering deposition are: the vacuum degree does not exceed 0.01Pa, the heating temperature of the substrate is 280-320°C, the insulation time is 25-35min, the argon pressure is 0.8-1.2Pa, the substrate bias is -50--70V, and the sputtering power is 40-50W.
[0017] Preferably, in step 2), each hexagonal unit is a large regular hexagon with a side length of 1.5 to 2 mm; the width of the groove is 300 to 400 μm, and the depth of the groove is 100 to 200 μm; a small regular hexagonal groove is provided in the middle of each large regular hexagonal unit, and the geometric centers of the large and small regular hexagons coincide; the side length of the small regular hexagonal groove is 0.6 to 0.8 mm, and the depth of the small regular hexagonal groove is 100 to 200 μm.
[0018] According to the above scheme, in step 2), the main process parameters of laser marking are: laser power of 20-50W, marking frequency of 20-40kHz, and marking speed of 200-800mm / s.
[0019] According to the above scheme, in step 3), the spherical powder is composed of lubricant Sn-Cu-Zn and reinforcing phase TiB2 in a mass ratio of 1:(0.015-0.02), and its particle size is 13-25 μm; the lubricant Sn-Cu-Zn is a tin-copper-zinc alloy, which is composed of 70-75 parts of Sn, 10-20 parts of Cu and 10-15 parts of Zn by mass.
[0020] According to the above scheme, in step 3), the main process parameters of high-temperature infiltration are: infiltration temperature is 350-400°C, vacuum degree is less than 0.01Pa, and insulation time is 20-30min.
[0021] According to the above scheme, the spherical powder containing the lubricant Sn-Cu-Zn and the reinforcing phase TiB2 is prepared by a rotating disk centrifugal atomization technology, and the preparation method mainly includes the following steps:
[0022] (1) Select 70-75 parts of Sn powder, 10-20 parts of Cu powder and 10-15 parts of Zn powder by weight, and then select TiB2 powder according to 1.5-2wt.% of the total weight of Sn powder, Cu powder and Zn powder, and then use vibration mixing to fully mix the four powders to obtain a mixture; wherein the vibration frequency is 45-55 Hz, the vibration force is 10000-12000 N, and the oscillation time is 30-40 min;
[0023] (2) melting the mixture obtained in step (1) under the protection of an inert gas to obtain a molten alloy liquid; wherein the melting temperature is 400 to 450° C.;
[0024] (3) Start the atomizing turntable. After the atomizer is operating normally, open the liquid release valve to put the molten alloy liquid into the atomizing turntable, and make the turntable rotate at high speed to obtain atomized molten droplets. The atomized molten droplets solidify to form spherical powder after cooling, and collect them in a receiving tank. After the spherical powder is fully cooled to room temperature, it is sieved according to the particle size requirement of 13 to 25 μm, which is the spherical powder containing lubricant Sn-Cu-Zn and reinforcing phase TiB2. Among them, the rotating disk speed is 26000 to 30000 r / min, and the molten alloy liquid flow rate is 1.0 to 1.2 kg / min;
[0025] The 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure obtained by the present invention has been subjected to friction experiments. The results show that it has excellent tribological properties in the process of friction and wear, with a small friction coefficient, an average value of about 0.16 to 0.19, and a wear rate of 2.9×10 -5 ~3.2×10 -5 mm 3 / (Nm).
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The film-forming behavior of the soft metal lubricating phase on the friction surface is random, so the coverage of the lubricating layer generated on the friction surface under complex working conditions such as wide temperature range and high load is usually insufficient. The present invention prepares an interface structure composed of a WS2 soft coating and a surface texture composite of a filling lubricant Sn-Cu-Zn and a reinforcing phase TiB2 on the surface of the metal substrate 42CrMo steel. A composite lubricating layer rich in WS2, Sn-Cu-Zn and TiB2 with sufficient coverage can be formed on the friction interface under a wide temperature range, thereby improving the stability of the lubrication performance of the friction interface under complex working conditions.
[0028] 2. Since the bearing capacity of the friction interface of the soft solid lubricant phase is weak, the geometric structural characteristics of the surface texture and the distribution of the solid lubricant phase at the friction interface have a significant impact on the tribological performance. The present invention optimizes the distribution and structural size parameters of the composite texture, designs a small regular polygonal groove in the middle of each regular hexagonal unit, and regulates the distribution position and area occupied by the composite texture filled with soft metal lubricant at the friction interface, so that the self-lubricating composite texture is fully and reasonably distributed at the friction interface, thereby achieving the beneficial effect of ensuring the bearing capacity of the friction interface while improving the lubrication performance.
[0029] 3. During the friction and wear process of the self-lubricating material described in the present invention, TiB2 forms a self-lubricating film on the friction surface together with the lubricants Sn-Cu-Zn and WS2 under the action of force-heat coupling; the friction reduction properties of the lubricants Sn-Cu-Zn and WS2 and the excellent wear resistance of TiB2 can play a synergistic role in friction reduction and wear resistance, thereby improving the tribological properties of the composite interface of the surface textured soft coating.
[0030] 4. In the present invention, WS2 with a typical layered structure is used as a soft coating, which can achieve flexible interlayer slip during the friction process; the soft metal lubricant Sn-Cu-Zn can form a soft metal film at the friction interface during the friction process, and the soft metal film has good self-repairing ability; the self-lubricating mechanism of the WS2 coating and the soft metal lubricant Sn-Cu-Zn is complementary, and the synergistic self-lubrication of the two can further reduce the friction and wear of the friction interface.
[0031] 5. Conventional soft metal lubricants often use expensive soft metal Ag. The soft metal composite lubricant Sn-Cu-Zn prepared by the present invention uses relatively low-priced soft metal materials Sn, Cu and Zn, which reduces the raw material cost of the lubricant, saves precious metal resources and is more conducive to the promotion and application of the present invention.
[0032] In summary, the present invention introduces the structural optimization of surface texture and the composite of soft metal lubricant-lubricating coating into the construction of new friction interfaces under complex working conditions such as wide temperature range and high load, and conducts comprehensive tribological design from both structural and material aspects, which is expected to expand the theory and method of solid lubrication design of mechanical parts. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a preparation process flow chart of the present invention.
[0034] Figure 2 It is a schematic diagram of the composite texture and its filling area, as well as the surface distribution of the soft coating and the schematic diagram of the AA section; Figure 2 In the figure, the upper figure is a schematic diagram of the surface distribution, and the lower figure is a cross-sectional diagram. The cross-sectional position and direction are Figure 2 The above picture is marked with AA.
[0035] Figure 3 This is a scanning electron microscope photograph of the spherical powder containing Sn-Cu-Zn and TiB2 prepared in Example 1 of the present invention, with a magnification of 2000 times.
[0036] Figure 4 This is an electron probe photograph of the wear scar of the 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure obtained in Example 2 of the present invention after a friction and wear experiment.
[0037] Figure 5 The figure shows the test results of the friction coefficient of the 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure obtained in Examples 1, 2, and 3 of the present invention using a ball-disc friction pair. The test conditions are: load 15-25N, sliding speed 0.2m / s, test temperature 25°C, sliding friction time 50min, grinding ball material GCr15 steel, and friction radius 5mm.
[0038] Figure 6 The figure shows the wear rate test results of the 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure prepared in Examples 1, 2, and 3 of the present invention using a ball-disc friction pair. The test conditions are: load 15-25N, sliding speed 0.2m / s, test temperature 25°C, sliding friction time 50min, grinding ball material GCr15 steel, and friction radius 5mm. DETAILED DESCRIPTION
[0039] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the present invention is not limited to the following embodiments.
[0040] In the following embodiments, the 42CrMo-based self-lubricating material with a composite interface structure of a surface textured soft coating is described, wherein the composite interface structure is composed of a WS2 soft coating and a surface composite texture of a filling lubricant Sn-Cu-Zn and a reinforcing phase TiB2. The present invention provides a specific preparation method, but does not limit the preparation method thereof. The 42CrMo-based self-lubricating material with a composite interface structure of a surface textured soft coating that meets the requirements of the present invention and is prepared by other methods also falls within the protection scope of the present invention.
[0041] Example 1
[0042] A 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure, using 42CrMo steel as a base material, forming a WS2 soft coating with a thickness of 50 μm on the surface of the base material; then preparing a composite texture on the surface of the 42CrMo steel with the WS2 coating; the composite texture is composed of a plurality of large regular hexagonal units arranged in a honeycomb shape, the side length of the large regular hexagon is 1.5 mm, and grooves are provided between any adjacent large regular hexagonal units, with a groove width of 300 μm and a groove depth of 100 μm, and a small regular hexagonal groove is provided in the middle of each large regular hexagonal unit, the geometric centers of the large and small regular hexagons coincide, the side length of the small regular hexagonal groove is 0.6 mm, and the depth of the small regular hexagonal groove is 100 μm, and the lubricant Sn-Cu-Zn and the reinforcing phase TiB2 are filled in the grooves of the composite texture and the small regular hexagonal grooves, such as Figure 2 shown.
[0043] like Figure 1 As shown, the preparation method of the 42CrMo-based self-lubricating material having a surface textured soft coating composite interface structure specifically comprises the following steps:
[0044] 1) The surface of the substrate 42CrMo steel is sandblasted to improve the bonding strength of the coating. The diamond grain size used for sandblasting is 120 mesh, and then ultrasonically cleaned with alcohol. After fully drying, the substrate after pretreatment is obtained;
[0045] 2) The substrate after the above pretreatment is placed in the vacuum chamber of the magnetron sputtering device, the vacuum degree is <0.01Pa, heated to 280°C, kept warm for 35 minutes, then argon gas is introduced, the WS2 target is turned on, and RF magnetron sputtering is adopted. The RF source frequency is 13.56MHz, the argon pressure is 0.8Pa, the substrate bias voltage is -50V, and the sputtering power is 40W; when the deposition thickness reaches 50μm, the WS2 target is turned off and the sputtering is stopped to obtain the WS2 soft coating.
[0046] 3) A composite texture was prepared on the surface of 42CrMo steel with WS2 coating by laser marking technology; wherein the composite texture consisted of a plurality of large regular hexagonal units arranged in a honeycomb shape, the side length of the large regular hexagon was 1.5 mm, and grooves were provided between any adjacent large regular hexagonal units, the groove width was 300 μm, the groove depth was 100 μm, and a small regular hexagonal groove was provided in the middle of each large regular hexagonal unit, the geometric centers of the large and small regular hexagons coincided, the side length of the small regular hexagonal groove was 0.6 mm, and the depth of the small regular hexagonal groove was 100 μm; the process parameters of laser marking were: laser power 20 W, marking frequency 20 kHz, and marking speed 200 mm / s.
[0047] 4) Select Sn powder, Cu powder and Zn powder in a mass ratio of 70:20:10 respectively, and then select TiB2 powder according to 1.5wt.% of the total mass of Sn powder, Cu powder and Zn powder, and use vibration mixing to fully mix the four powders; wherein, the vibration frequency is 45Hz, the vibration force is 10000N, and the oscillation time is 30min; the fully mixed powders are melted under the protection of inert gas argon at a melting temperature of 400°C to obtain a molten alloy liquid.
[0048] 5) Start the atomizing turntable, open the liquid release valve to place the molten alloy liquid onto the high-speed rotating atomizing turntable, and atomize the molten alloy liquid in the atomizer. The flow rate of the molten alloy liquid is 1.0 kg / min, and the rotation speed of the rotating disk is 26000 r / min. The molten droplets obtained by atomization are cooled and solidified to form spherical powder, that is, spherical powder containing Sn-Cu-Zn and TiB2, which is collected in a receiving tank. After the spherical powder is fully cooled to room temperature, spherical powder with a particle size range of 13 to 25 μm is screened out for use in the subsequent steps of this embodiment, such as Figure 3 shown.
[0049] 6) The spherical powder containing Sn-Cu-Zn and TiB2 is infiltrated and filled into the grooves and small regular hexagonal grooves of the composite texture by high temperature infiltration technology, thereby forming the 42CrMo-based self-lubricating material with a surface texture soft coating composite interface structure. The process parameters of high temperature infiltration are: infiltration temperature 350°C, vacuum degree <0.01Pa, and holding time 30min.
[0050] The friction and wear test of the 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure prepared in Example 1 was carried out using a ball-disc friction pair. The test conditions were: load 15N, sliding speed 0.2m / s, test temperature 25°C, sliding friction time 50min, grinding ball material GCr15 steel, and friction radius 5mm.
[0051] Figure 5 and 6 It shows that the friction coefficient of the 42CrMo-based self-lubricating composite material with a surface textured soft coating composite interface structure prepared in this example is small, with an average value of about 0.18 and a wear rate of 3.1×10 -5 mm 3 / (Nm), reflecting excellent tribological properties.
[0052] Example 2
[0053] A 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure, comprising 42CrMo steel as a base material, a WS2 soft coating with a thickness of 70 μm formed on the surface of the base material; and then a composite texture is prepared on the surface of the 42CrMo steel with the WS2 coating; the composite texture is composed of a plurality of large regular hexagonal units arranged in a honeycomb shape, the side length of the large regular hexagon is 1.8 mm, grooves are provided between any adjacent large regular hexagonal units, the groove width is 350 μm, the groove depth is 150 μm, and a small regular hexagonal groove is provided in the middle of each large regular hexagonal unit, the geometric centers of the large and small regular hexagons coincide, the side length of the small regular hexagonal groove is 0.7 mm, the depth of the small regular hexagonal groove is 150 μm, and the lubricant Sn-Cu-Zn and the reinforcing phase TiB2 are filled in the grooves of the composite texture and the small regular hexagonal grooves.
[0054] The preparation method of the 42CrMo-based self-lubricating material having a surface textured soft coating composite interface structure specifically comprises the following steps:
[0055] 1) The surface of the substrate 42CrMo steel is sandblasted to improve the bonding strength of the coating. The diamond grain size used for sandblasting is 130 mesh, and then ultrasonically cleaned with alcohol. After sufficient drying, the pre-treated substrate is obtained;
[0056] 2) The substrate after the above pretreatment is placed in the vacuum chamber of the magnetron sputtering device with a vacuum degree of <0.01Pa, heated to 300°C, kept warm for 30min, then introduced with argon gas, turned on the WS2 target, and adopted RF magnetron sputtering with an RF source frequency of 13.56MHz, an argon pressure of 1.0Pa, a substrate bias of -60V, and a sputtering power of 45W; when the deposition thickness reaches 70μm, the WS2 target is turned off and the sputtering is stopped to obtain the WS2 soft coating.
[0057] 3) Composite textures were prepared on the surface of 42CrMo steel with WS2 coating by laser marking technology. The composite texture is composed of a plurality of large regular hexagonal units arranged in a honeycomb shape, the side length of the large regular hexagon is 1.8 mm, and grooves are provided between any adjacent large regular hexagonal units, with a groove width of 350 μm and a groove depth of 150 μm, and a small regular hexagonal groove is provided in the middle of each large regular hexagonal unit, the geometric centers of the large and small regular hexagons coincide, the side length of the small regular hexagonal groove is 0.7 mm, and the depth of the small regular hexagonal groove is 150 μm; the process parameters of laser marking are: laser power 40 W, marking frequency 30 kHz, and marking speed 500 mm / s.
[0058] 4) Select Sn powder, Cu powder and Zn powder in a mass ratio of 70:15:15 respectively, and then select TiB2 powder at 1.75wt.% of the total mass of Sn powder, Cu powder and Zn powder, and use vibration mixing to fully mix the four powders; wherein, the vibration frequency is 50Hz, the vibration force is 11000N, and the oscillation time is 35min; the fully mixed powders are melted under the protection of inert gas argon at a melting temperature of 425°C to obtain a molten alloy liquid.
[0059] 5) Start the atomizing turntable, open the liquid valve to put the molten alloy liquid into the high-speed rotating atomizing turntable, and atomize the molten alloy liquid in the atomizer. The flow rate of the molten alloy liquid is 1.1 kg / min, and the rotating disk speed is 28000 r / min. The atomized molten droplets are cooled and solidified to form spherical powder, that is, spherical powder containing Sn-Cu-Zn and TiB2, which is collected in a receiving tank. After the spherical powder is fully cooled to room temperature, spherical powder with a particle size range of 13-25 μm is screened out for subsequent steps of this embodiment.
[0060] 6) The spherical powder containing Sn-Cu-Zn and TiB2 is infiltrated and filled into the grooves and small regular hexagonal grooves of the composite texture by high-temperature infiltration technology, thereby forming the 42CrMo-based self-lubricating material with a surface texture soft coating composite interface structure. The high-temperature infiltration process used is: infiltration temperature 375°C, vacuum degree <0.01Pa, and holding time 25min.
[0061] The 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure prepared in Example 2 was subjected to a friction and wear test using a ball-on-disc friction pair. The test conditions were: load 20 N, sliding speed 0.2 m / s, test temperature 25°C, sliding friction time 50 min, grinding ball material GCr15 steel, and friction radius 5 mm.
[0062] Depend on Figure 4 The wear scar image of the 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure obtained after the friction and wear experiment shows that the wear scar surface is smooth and flat. Figure 5 and 6 It shows that the 42CrMo-based self-lubricating composite material with a surface textured soft coating composite interface structure prepared in this example has a small friction coefficient (average value is about 0.16) and a wear rate of 2.9×10 -5 mm 3 / (Nm), reflecting excellent tribological properties.
[0063] Example 3
[0064] A 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure, with 42CrMo steel as a base material, a WS2 soft coating with a thickness of 80 μm formed on the surface of the base material; then a composite texture is prepared on the surface of the 42CrMo steel with the WS2 coating; the composite texture is composed of a plurality of large regular hexagonal units arranged in a honeycomb shape, the side length of the large regular hexagon is 2 mm, grooves are provided between any adjacent large regular hexagonal units, the groove width is 400 μm, the groove depth is 200 μm, and a small regular hexagonal groove is provided in the middle of each large regular hexagonal unit, the geometric centers of the large and small regular hexagons coincide, the side length of the small regular hexagonal groove is 0.8 mm, the depth of the small regular hexagonal groove is 200 μm, and the lubricant Sn-Cu-Zn and the reinforcing phase TiB2 are filled in the grooves of the composite texture and the small regular hexagonal grooves.
[0065] The preparation method of the 42CrMo-based self-lubricating material having a surface textured soft coating composite interface structure specifically comprises the following steps:
[0066] 1) The surface of the substrate 42CrMo steel is sandblasted to improve the bonding strength of the coating. The diamond grain size used for sandblasting is 140 mesh, and then ultrasonically cleaned with alcohol. After sufficient drying, the substrate after pretreatment is obtained;
[0067] 2) The substrate after the above pretreatment is placed in the vacuum chamber of the magnetron sputtering device with a vacuum degree of <0.01Pa, heated to 320°C, kept warm for 25min, then introduced with argon gas, turned on the WS2 target, and adopted RF magnetron sputtering with a RF source frequency of 13.56MHz, an argon pressure of 1.2Pa, a substrate bias of -70V, and a sputtering power of 50W; when the deposition thickness reaches 80μm, the WS2 target is turned off and the sputtering is stopped to obtain the WS2 soft coating.
[0068] 3) A composite texture was prepared on the surface of 42CrMo steel with WS2 coating by laser marking technology; wherein the composite texture consisted of a plurality of large regular hexagonal units arranged in a honeycomb shape, the side length of the large regular hexagon was 2 mm, and grooves were provided between any adjacent large regular hexagonal units, the groove width was 400 μm, the groove depth was 200 μm, and a small regular hexagonal groove was provided in the middle of each large regular hexagonal unit, the geometric centers of the large and small regular hexagons coincided, the side length of the small regular hexagonal groove was 0.8 mm, and the depth of the small regular hexagonal groove was 200 μm; the laser marking process parameters were: laser power 50 W, marking frequency 40 kHz, and marking speed 800 mm / s.
[0069] 4) Select Sn powder, Cu powder and Zn powder in a mass ratio of 75:15:10 respectively, and then select TiB2 powder according to 2wt.% of the total mass of Sn powder, Cu powder and Zn powder, and use vibration mixing to fully mix the four powders; wherein, the vibration frequency is 55Hz, the vibration force is 12000N, and the oscillation time is 40min; the fully mixed powders are melted under the protection of inert gas argon at a melting temperature of 450°C to obtain a molten alloy liquid.
[0070] 5) Start the atomizing turntable, open the liquid valve to put the molten alloy liquid into the high-speed rotating atomizing turntable, and atomize the molten alloy liquid in the atomizer. The flow rate of the molten alloy liquid is 1.2 kg / min, and the rotating disk speed is 30000 r / min. The atomized molten droplets are cooled and solidified to form spherical powder, that is, spherical powder containing Sn-Cu-Zn and TiB2, which is collected in a receiving tank. After the spherical powder is fully cooled to room temperature, spherical powder with a particle size range of 13 to 25 μm is screened out for subsequent steps of this embodiment.
[0071] 6) The spherical powder containing Sn-Cu-Zn and TiB2 is infiltrated and filled into the grooves and small regular hexagonal grooves of the composite texture by high-temperature infiltration technology, thereby forming the 42CrMo-based self-lubricating material with a surface texture soft coating composite interface structure. The high-temperature infiltration process used is: infiltration temperature 400°C, vacuum degree <0.01Pa, and holding time 20min.
[0072] The 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure prepared in Example 3 was subjected to a friction and wear test using a ball-on-disc friction pair. The test conditions were: load 25 N, sliding speed 0.2 m / s, test temperature 25°C, sliding friction time 50 min, grinding ball material GCr15 steel, and friction radius 5 mm.
[0073] Figure 5 and 6 It shows that the 42CrMo-based self-lubricating composite material with a surface textured soft coating composite interface structure prepared in this example has a small friction coefficient (average value is about 0.19) and a wear rate of 3.2×10 -5 mm 3 / (Nm), reflecting excellent tribological properties.
[0074] According to the experimental results of the above three embodiments, it is shown that the 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure obtained by the present invention exhibits excellent tribological properties during the friction and wear process, with a small friction coefficient (average value of about 0.16-0.19) and a wear rate of 2.9-3.2×10 -5 mm 3 / (Nm).
[0075] In summary, the present invention adopts magnetron sputtering deposition process to prepare WS2 soft coating on 42CrMo steel substrate material; adopts laser marking process technology to prepare structurally optimized groove texture and groove texture on the surface of 42CrMo steel deposited with WS2 coating; finally adopts high temperature infiltration process technology to fill soft metal lubricant Sn-Cu-Zn and reinforcing phase TiB2 in the composite texture groove, thereby obtaining a 42CrMo-based self-lubricating material with a composite interface structure of surface texture soft coating. The 42CrMo-based self-lubricating material with a composite interface structure of surface texture soft coating described in the present invention introduces the structural optimization of surface texture and the composite of soft metal lubricant-lubricating coating into the construction of a new friction interface, improves the lubrication performance while ensuring the interface bearing capacity, and the prepared 42CrMo-based self-lubricating material has a low friction coefficient and wear rate during the friction and wear process, which can effectively improve the tribological properties of 42CrMo steel material.
[0076] All raw materials listed in the present invention can realize the present invention, and the upper and lower limits and interval values of each raw material can realize the present invention. The upper and lower limits and interval values of the surface texture structure design parameters (such as side length, width and depth, etc.) and the 42CrMo-based self-lubricating material preparation process parameters (such as temperature, rotation speed, power, time and frequency, etc.) described in the present invention can realize the present invention. The embodiments are not listed one by one here.
[0077] The above is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several improvements and changes without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure, characterized in that It uses 42CrMo steel as a base material, deposits a WS2 soft coating on the surface of the base material, and the surface of the WS2 soft coating is processed with a composite texture; the composite texture is composed of a plurality of hexagonal units arranged in a honeycomb shape, grooves are provided between any adjacent hexagonal units, and a regular polygonal groove is provided in the middle of each hexagonal unit; the grooves and regular polygonal grooves of the composite texture are filled with lubricant Sn-Cu-Zn and reinforcing phase TiB2.
2. The 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure according to claim 1, characterized in that: The groove depth and regular polygonal groove depth of the composite texture are both greater than the thickness of the WS2 soft coating.
3. The 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure according to claim 1, characterized in that: Each hexagonal unit is a regular hexagon with a side length of 1.5 to 2 mm; the width of the groove is 300 to 400 μm, and the depth of the groove is 100 to 200 μm; a regular polygonal groove is provided in the middle of each regular hexagonal unit, and the regular polygonal groove coincides with the geometric center of the regular hexagonal unit; the side length of the regular polygonal groove is 0.6 to 0.8 mm, and the depth of the regular polygonal groove is 100 to 200 μm.
4. The 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure according to claim 1, characterized in that: The thickness of the WS2 soft coating is 50-80 μm; the regular polygonal groove is a regular hexagonal groove.
5. The method for preparing the 42CrMo-based self-lubricating material according to any one of claims 1 to 4, characterized in that: The main steps are as follows: 1) The WS2 soft coating was prepared on the surface of the substrate 42CrMo steel by magnetron sputtering deposition process; 2) Using laser marking technology to process composite textures on the surface of WS2 soft coating; 3) Spherical powder containing lubricant Sn-Cu-Zn and reinforcing phase TiB2 is infiltrated and filled into the grooves and regular polygonal grooves of the composite texture by a high-temperature infiltration process, thereby forming the 42CrMo-based self-lubricating material with a surface textured soft coating composite interface structure.
6. The preparation method according to claim 5, characterized in that: The main process parameters of magnetron sputtering deposition are: vacuum degree not exceeding 0.01Pa, substrate heating temperature of 280-320℃, holding time of 25-35min, argon pressure of 0.8-1.2Pa, substrate bias of -50--70V, and sputtering power of 40-50W.
7. The preparation method according to claim 5, characterized in that: The main process parameters of laser marking are: laser power of 20-50W, marking frequency of 20-40kHz, and marking speed of 200-800mm / s.
8. The preparation method according to claim 5, characterized in that: The spherical powder is composed of lubricant Sn-Cu-Zn and reinforcing phase TiB2 in a mass ratio of 1:(0.015-0.02), and its particle size is 13-25 μm; the lubricant Sn-Cu-Zn is a tin-copper-zinc alloy, which is composed of 70-75 parts of Sn, 10-20 parts of Cu and 10-15 parts of Zn by mass.
9. The preparation method according to claim 5, characterized in that: The main process parameters of high-temperature infiltration are: infiltration temperature of 350-400°C, vacuum degree less than 0.01Pa, and insulation time of 20-30min.